Investigating Semantics Activities in New Pandemic Era 2021 - Widiya Juliyanti; Fonnalita Fonnalita; Rialisa Triananda Triananda; Pina Barokah; Roselia Putri Lestari (EDULIA: English Education, Linguistic and Art Journal, 2021)
This study aimed to describe semantic activities in the new pandemic era in 2021 at STKIP PGRI Lubuklinggau. In this research, researchers used descriptive qualitative research. The subject of this research is semantics lecturer. The researcher chose one research subject because the semantic lecturer is a key informant who has met the requirements as a key informant. Based on research results, the researchers discovered how semantics the lecturer teaches starting from the approach. Semantics lecturer combines two languages, English and Bahasa Indonesia, considered avoiding misunderstanding communication and help students to understand the materials more. In conculsions, there is no difference between online and offline syllabus. The material remains the same. The differences only about how the way the lecturer delivers the material, method, and learning strategies. Keywords: Activities, Pandemic, Semantics